Volume 2: Turbo Expo 2002, Parts a and B 2002
DOI: 10.1115/gt2002-30140
|View full text |Cite
|
Sign up to set email alerts
|

Brayton or Brayton-Rankine Combined Cycle With Hot-Gas Recirculation and Inverse Mixing Ejector

Abstract: An open/closed gas-turbine simple Brayton cycle or Brayton-Rankine gas- and steam-turbine combined-cycle power-producing system is proposed, with the gas turbine recirculating a large portion of partly expanded high-temperature gas into an inverse mixing ejector. The inverse mixing ejector uses injected-gas velocity that is necessarily greater than jet-gas velocity to increase the hot-gas pressure up to the compressor-discharge level. This is a necessary condition for achieving very high cycle thermal efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Consequently, two ejector designs were proposed to fulfil the ejector requirements defined in the paper of Padilla et al [12]. The mentioned authors adopted idea of introducing the ejector into the system from the study presented in [30]. They also suggested that the investigated ejector equipped cycle can be integrated with Concentrated Solar Thermal system.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, two ejector designs were proposed to fulfil the ejector requirements defined in the paper of Padilla et al [12]. The mentioned authors adopted idea of introducing the ejector into the system from the study presented in [30]. They also suggested that the investigated ejector equipped cycle can be integrated with Concentrated Solar Thermal system.…”
Section: Introductionmentioning
confidence: 99%